Integration of Two Skeptical Emotion Theories: Dimensional Appraisal Theory and Russell's Psychological Construction Theory. Issue 1 (2nd January 2017) - Moors, Agnes
ABSTRACT: This inquiry attempts to integrate two skeptical emotion theories: dimensional appraisal theory and Russell's (2003) psychological construction theory. To bring out the skeptical elements of these theories, I compare them first with two classic theories: affect program theory and discrete appraisal theory. The skeptical theories are similar to each other in that they replace the concept of emotion with the concept of emotional episode, and that they organize the variety within the set of emotional episodes according to dimensions instead of vernacular emotion subsets. Their differences concern the strength of the relations among the components in emotional episodes and the scientific status of the set of emotional episodes. To make an informed decision about the elements to keep and to revise from both theories, I engage in a separate analysis of the behavior-related components and the experience component, guided by insights from general behavior theories and general theories of consciousness. The analysis of the behavior-related components suggests the relatively uncharted idea that the so-called emotional aspect of behavior can be caused by a goal-directed mechanism. The analysis of the experience component reveals that different theories have emphasized different aspects of experience and hence different paths toward experience. The inquiry ends with an integrated theory that rejects the scientific status of emotions or emotional episodes, but accepts the scientific status of the components and sees strong causal relations among them.